Fiscal Decentralization, Commitment and Regional Inequality: Evidence from State-level Cross-sectional Data for the United States - Akai, Nobuo; Hosio, Masayo (Journal of Income Distribution®, 2009)
Conventional approaches to fiscal decentralization suggest that decentralization lowers the power of redistribution, but recent theories argue that fiscal decentralization can work as a commitment device. The former effect is argued to cause an increase in inter-county inequality, while the latter suggests a decrease. This article first clarifies the relationship between fiscal decentralization and inter-county inequality by using cross-sectional data for the United States. Our result indicates that the achievement of autonomy by fiscal decentralization in poor (low-income) counties contributes to decreased inter-county inequality, but that this effect is not as large as the dominating adverse effect fiscal decentralization has on rich (highincome) counties.